Room Temperature Magnetic Switchability Assisted by Hysteretic Valence Tautomerism in a Layered Two-Dimensional Manganese-Radical Coordination Framework - Lannes, Anthony; Suffren, Yan; Tommasino, Jean Bernard; Chiriac, Rodica; Toche, François; Khrouz, Lhoussain; Molton, Florian; Duboc, Carole; Kieffer, Isabelle; Hazemann, Jean-Louis; Reber, Christian; Hauser, Andreas; et al. (Journal of the American Chemical Society, 2016)
The manganese-nitronyl-nitroxide two-dimensional coordination polymer {[Mn (NITIm) ]ClO } (1) (NITImH = 2-(2-imidazolyl)-4,4,5,5-tetramethyl-4,5-dihydro-1H-3-oxide-1-oxyl) undergoes an unusual hysteretic thermo-induced valence tautomeric transition near room temperature, during which the manganese(II) ions are oxidized to manganese(III) and two of the three deprotonated radicals (NITIm ) are reduced to their diamagnetic aminoxyl form (denoted NIT ). Upon cooling, the high-temperature species {[Mn (NITIm) ]ClO } (1 ) turns into the low-temperature species {[Mn (NIT ) (NITIm)]ClO } (1 ) around 274 K, while on heating the process is reversed at about 287 K. This valence tautomeric phenomenon is supported by temperature-dependent magnetic susceptibility measurements, differential scanning calorimetry (DSC), crystal structure determination, UV-vis absorption, X-ray absorption (XAS), and emission (XES) and electron paramagnetic resonance (EPR) spectroscopies in the solid state.